2020
DOI: 10.1302/2046-3758.98.bjr-2020-0017.r2
|View full text |Cite
|
Sign up to set email alerts
|

A lean bioabsorbable magnesium-zinc-calcium alloy ZX00 used for operative treatment of medial malleolus fractures

Abstract: Aims This study is a prospective, non-randomized trial for the treatment of fractures of the medial malleolus using lean, bioabsorbable, rare-earth element (REE)-free, magnesium (Mg)-based biodegradable screws in the adult skeleton. Methods A total of 20 patients with isolated, bimalleolar, or trimalleolar ankle fractures were recruited between July 2018 and October 2019. Fracture reduction was achieved through bioabsorbable Mg-based screws composed of pure Mg alloyed with zinc (Zn) and calcium (Ca) ( Mg-Zn0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“… 84 The corrosion products (mainly Mg 2+ ions) interact with chloride ions in the body fluid or are digested by macrophages. 49 However, during the early stages of Mg implantation, it corrodes quicker, causing an implant mechanical instability. This occurs owing to the lack of MgO + Mg(OH) 2 protective layer on the fresh surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 84 The corrosion products (mainly Mg 2+ ions) interact with chloride ions in the body fluid or are digested by macrophages. 49 However, during the early stages of Mg implantation, it corrodes quicker, causing an implant mechanical instability. This occurs owing to the lack of MgO + Mg(OH) 2 protective layer on the fresh surface.…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 Biodegradable alloys made of Mg, zinc (Zn), and calcium (Ca), known as Mg-Zn-Ca ternary or ZX alloys, are among the most recent developed Mg-based alloys that have gained attention in the field. 7 , 48 51 Theoretically, due to the presence of all three elements in the body, the organism could metabolize the implanted alloy safely. 52 Cipriano et al 53 studied the influence of degradation products over time on bone cell functions and reported that the ZX alloys can increase the cell functions toward new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fast in vivo degradation, some trials investigated the use of pure Mg in the femoral head [ 86 , 89 , 106 ] and in the metatarsus [ 101 ]. ZX00, a lean Mg-Ca-Zn was also evaluated in a prospective pilot study for medial malleolar fractures [ 108 ]. Another alloy made with Mg-Ca-Zn, was studied as bioresorbable Mg alloy screws for hand fractures requiring internal fixation [ 87 ].…”
Section: Clinical Evaluation Of Mg-based Alloysmentioning
confidence: 99%
“…Upon resorption, Mg and its alloy release Mg 2+ ions, which are either stored in bone or released into the circulation, thereby potentially resulting in the manifestation of hypermagnesemia. However, Holweg et al demonstrated the normal range of Mg concentration in the blood up to 12 weeks after Mg-based screw fixation in 20 patients [ 108 ]. This Mg blood level assessment was confirmed by two other trials [ 85 , 89 ].…”
Section: Clinical Evaluation Of Mg-based Alloysmentioning
confidence: 99%
See 1 more Smart Citation